MOBA Online Games As an Interactive Media to Develop EFL Learners’ Speaking Skills - Teguh Prasetyo (Universitas Negeri Surabaya, 2024)
Speaking is the most challenging of the four fundamental skills for students, particularly those learning English as a second language. One factor that makes it difficult for learners to develop their speaking skills is the lack of opportunities to explore their abilities outside the classroom. In this digital era, learners must utilize all the tools to assist their speaking skills, including MOBA games. This study aims to determine whether MOBA games can be used to practice the learners' speaking ability, the language expression used, and the obstacles that the learners experienced when practicing speaking using MOBA games. The research method uses a qualitative case study with participants of 3 university students in Surabaya. The data collection technique uses interviews with 21 questions related to MOBA games to practice speaking, and the researcher also uses observation to get more data. The study's result showed positive feedback from the participant that MOBA games can be used as media to assist their speaking skills outside the classroom. Furthermore, the study also revealed that the learners mainly used short dialog as language expression when playing MOBA games, such as imperative sentences and repetition. In addition, it was found that the learners experienced obstacles such as toxicity and laziness while using MOBA as the media to develop their speaking skills.